Prevalence and risk factors for chronic kidney disease in primary health care in the southern region of New Zealand. Issue 3 (27th February 2019) - Lloyd, Hywel; Li, Grace; Tomlin, Andrew; Tilyard, Murray W; Walker, Robert; Schollum, John
ABSTRACT: Aim: While the prevalence of end stage kidney disease in New Zealand (NZ) is well defined, the prevalence of chronic kidney disease (CKD) in NZ is unknown. To estimate the prevalence of and risk factors for CKD in the southern region of New Zealand. Methods: A retrospective electronic health record cohort study using data from the Southern Primary Care register covering 94% of the population. Patients, 20 years or older were identified and linked to laboratory results for serum creatinine and urinary albumin excretion. Chronic kidney disease was defined as an estimated glomerular filtration rate of less than 60 mL/min per 1.73 m 2 (G3‐5) or the presence of albuminuria of greater than 3 mg/mmol (A2‐3). Diabetes was identified from a national virtual diabetes database. From this, we estimated the prevalence of CKD by age, gender, ethnicity, deprivation and the presence of diabetes mellitus. Results: Of a total adult population of 211 980, 159 799 had a serum creatinine checked and 27 905 had an estimate of albuminuria. The estimated prevalence of CKD was 11.8%. 6.3% of total population had CKD stage G3a, 2.4% G3b, 0.8% G4, 0.2% G5, 1.8% A2 albuminuria and 0.3% A3 albuminuria. Increasing age, female sex, ethnic group, social deprivation and diabetes mellitus were associated with an increased risk of CKD. 11 351 patients had a diagnosis of diabetes mellitus and were almost universally tested (99.3%) for CKD. The presence of albuminuria was strongly correlated with ethnic group, male sex and living in a deprived area. The retrospective electronic health record study with associated selection and testing bias are potential limitations of the present study. Conclusion: Chronic kidney disease prevalence in this region appears to be similar to other reported populations. The majority of those at risk for CKD were tested for reduced eGFR. The presence of albuminuria, an integral component of CKD diagnostic criteria, was under utilized in the non‐diabetic population. Summary at a Glance: This is the first description of CKD in the community setting in New Zealand. In general, rates are comparable to other countries. Key predictors for the risks of CKD were older age and increasing social deprivation.